A qualitative study to control adolescent smoking behaviour in junior high school - Wiwin Haryati; Junaiti Sahar; Etty Rekawati; Besral (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate efforts made to help young people curb smoking behaviour. Method: The qualitative study was conducted from January to February 2020 at 3 junior high schools in Banda Aceh, Indonesia, after approval from the ethics review committee of the University of Indonesia. The participants were students in grades 7 and 8. Data was collected through interviews, documentation and field notes. Data was subjected to construct and content validation, and was qualitatively analysed using NVivo 12 Plus. Results: Of the 16 students, 2(12.5%) were from grade 7, and 14(87.5%) from grade 8. Overall, 12(75%) adolescents had smoked. There were 5 themes that emerged: smoking compulsion, adolescent perspectives on smoking behaviour, knowledge of the risks associated with smoking, obstacles to quitting, and smoking control strategies. To curb adolescent smoking, there were 2 themes: barriers to quitting smoking, and smoking control strategies. Conclusion: Efforts to curb smoking should focus on increasing adolescent self-control. Keywords: Smoking, Schools, Students, Adolescents.